2013
DOI: 10.1556/oh.2013.29545
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo cardiomyopathy: a novel beta-adrenergic blocker withdrawal syndrome

Abstract: The authors describe two cases of takotsubo cardiomyopathy developing after an abrupt withdrawal of carvedilol and bisoprolol. Takotsubo or stress cardiomyopathy is characterized by acute and reversible cardiac dysfunction without coronary artery disease. It is triggered by acute emotional or physical stress, drugs or drug withdrawal. The immediate discontinuation of the long acting vasodilator beta-blocker, carvedilol has not yet been described to cause takotsubo cardiomyopathy. The authors recommend cautious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Other suggested mechanisms are, coronary artery vasospasm and microvascular dysfunction [2,5]. Additionally, there have been case reports associating cephalosporins, analgesics and withdrawal from beta blockers with the syndrome [10][11][12]. In a review by Pedro Amariles, 20 drugs were identified as possible causes of TTC.…”
Section: Discussionmentioning
confidence: 99%
“…Other suggested mechanisms are, coronary artery vasospasm and microvascular dysfunction [2,5]. Additionally, there have been case reports associating cephalosporins, analgesics and withdrawal from beta blockers with the syndrome [10][11][12]. In a review by Pedro Amariles, 20 drugs were identified as possible causes of TTC.…”
Section: Discussionmentioning
confidence: 99%
“…87 Phentermine is an amphetamine derivative used as an appetite suppressant, which is thought to be a sympathomimetic amines that stimulate the release of norepinephrine and dopamine from the storage sites in the presynaptic nerve terminals. 119 Other catecholamine-related causes included indirect adrenergic effects, including parasympathetic block (2 cases), 117,122 sudden withdrawal of b-blockers (3 cases), 76,77 anaphylactic reactions (5 cases), [81][82][83][84]118 withdrawal of opioids (5 cases), 69,70,75,78,79 or alcohol (2 cases). 71,125 Opioid withdrawal is known to cause hyperadrenergic state that leads to catecholamine surge and increased b-receptor sensitivity and subsequently myocardial stunning.…”
Section: Discussionmentioning
confidence: 99%
“…In that paper, classical features of TCM were observed, including cardiac isoenzyme elevation, QTc interval prolongation, rapidly reversible cardiac dysfunction, and left ventricular ballooning variants [12]. Rarely, abrupt withdrawal of long-acting beta blockers may lead to TCM [13]. …”
Section: Discussionmentioning
confidence: 99%